A MAGNETOHYDRODYNAMIC STUDY OF BEHAVIOR IN AN ELECTROLYTE FLUID USING NUMERICAL AND EXPERIMENTAL SOLUTIONS - Aoki, L. P.; Maunsell, M. G.; Schulz, H. E. (Revista de Engenharia Térmica, 2012)
This article examines a rectangular closed circuit filled with an electrolyte fluid, known as macro pumps, where a permanent magnet generates a magnetic field and electrodes generate the electric field in the flow. The fluid conductor moves inside the circuit under magnetohydrodynamic effect (MHD). The MHD model has been derived from the Navier Stokes equation and coupled with the Maxwell equations for Newtonian incompressible fluid. Electric and magnetic components engaged in the test chamber assist in creating the propulsion of the electrolyte fluid. The electromagnetic forces that arise are due to the cross product between the vector density of induced current and the vector density of magnetic field applied. This is the Lorentz force. Results are present of 3D numerical MHD simulation for newtonian fluid as well as experimental data. The goal is to relate the magnetic field with the electric field and the amounts of movement produced, and calculate de current density and fluid velocity. An u-shaped and m-shaped velocity profile is expected in the flows. The flow analysis is performed with the magnetic field fixed, while the electric field is changed. Observing the interaction between the fields strengths, and density of the electrolyte fluid, an optimal configuration for the flow velocity is determined and compared with others publications.